2020
DOI: 10.1177/0272989x20935864
|View full text |Cite
|
Sign up to set email alerts
|

A Modern Dilemma: How Experts Grapple with Ambiguous Genetic Test Results

Abstract: Objective. Clinicians regularly use panel genetic testing to identify hereditary breast cancer risk, but this practice increases the rate of receiving an ambiguous test result, the variant of uncertain significance (VUS). VUS results are a growing and long-term challenge for providers and have caused negative patient outcomes. The objective of this study was to elicit expert opinions about patients’ decision making after receiving a VUS result to provide future guidance for VUS disclosure. Methods. Using an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…(2020) recently found that strategies used by genetic counselors to communicate uncertainty regarding genetic testing results included three core themes: being open and honest, adapting to patients’ needs, and focusing on what is known. Another recent study found that HCP's address VUSs with breast cancer patients through 2 main categories: ambiguity and risk management (Scherr et al., 2020). Ambiguity management included, for example, discussing the opportunity to participate in research studies, clinical DNA banking, expanded genetic testing, additional clinical evaluations, and maintaining contact with the provider who ordered the test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) recently found that strategies used by genetic counselors to communicate uncertainty regarding genetic testing results included three core themes: being open and honest, adapting to patients’ needs, and focusing on what is known. Another recent study found that HCP's address VUSs with breast cancer patients through 2 main categories: ambiguity and risk management (Scherr et al., 2020). Ambiguity management included, for example, discussing the opportunity to participate in research studies, clinical DNA banking, expanded genetic testing, additional clinical evaluations, and maintaining contact with the provider who ordered the test.…”
Section: Discussionmentioning
confidence: 99%
“…Such a narrative demonstrates the customization of specific variants through a plot that begins with a mystery, develops through clinical discussions and research analyses, and hopefully ends with a resolution of the causal ambiguity (or not, in this case). It should remind us that providing the patient with an action they could take based on the VUS, which may be recommended for reducing ambiguity (Scherr et al., 2020), does not always correspond with a beneficial coping strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation